Green Synthesis of Highly Luminescent Carbon Quantum Dots from Lemon Juice - Bui Thi Hoan; Phuong Dinh Tam; Vuong-Hung Pham (Journal of Nanotechnology)
Highly luminescent carbon dots (C-dots) were synthesized by the one-pot simple hydrothermal method directly from lemon juice using different temperatures, time, aging of precursors, and diluted solvents to control the luminescence of C‐dots. The obtained C-dots were characterized by high-resolution transmission electron microscopy, X-ray photoelectron spectroscopy, Fourier transform infrared spectrophotometry, dynamic light scattering, ultraviolet-visible spectrophotometry, and photoluminescent spectrophotometry. The results show that C‐dots had strong green light emission with quantum yield in the range of 14.86 to 24.89% as a function of hydrothermal temperatures. Furthermore, light emission that is dependent on hydrothermal time, aging of precursor, and diluted solvent was observed. These results suggest that the C‐dots have potential application in optoelectronics and bioimaging.